2007
DOI: 10.1037/1541-1559.4.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Timing of postcombat mental health assessments.

Abstract: 509 Army Soldiers (who had returned within the previous week from a 12-month deployment to Iraq) participated in a study to examine changes in psychological symptoms between homecoming and 120 days later. Rates of psychological symptoms were significantly higher at 120 days postdeployment than at immediate reintegration largely due to an increase in Soldiers who were initially nonsymptomatic but became symptomatic later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 22 publications
6
146
2
1
Order By: Relevance
“…Regarding the finding of reduced depression symptomatology at Time 2, there was little actual change in the mean level of depression symptomatology reported over time among the deployers, but by comparison, depression symptom levels increased from Time 1 to Time 2 among nondeployers (see table 2). Other prospective deployment studies have documented a homecoming effect, characterized by improved mood and other psychological symptoms when assessed most proximal to re-deployment (60). Although over 90% of the deployed group was assessed within 7-8 days of their return from Bosnia, no widespread evidence of a significant homecoming effect on mood and performance patterns was observed in this study.…”
Section: Proctor Et Alcontrasting
confidence: 47%
“…Regarding the finding of reduced depression symptomatology at Time 2, there was little actual change in the mean level of depression symptomatology reported over time among the deployers, but by comparison, depression symptom levels increased from Time 1 to Time 2 among nondeployers (see table 2). Other prospective deployment studies have documented a homecoming effect, characterized by improved mood and other psychological symptoms when assessed most proximal to re-deployment (60). Although over 90% of the deployed group was assessed within 7-8 days of their return from Bosnia, no widespread evidence of a significant homecoming effect on mood and performance patterns was observed in this study.…”
Section: Proctor Et Alcontrasting
confidence: 47%
“…It is possible that in addition to improving work-related outcomes (e.g., job performance, Luthans et al, 2010), such interventions could also help reduce the rates of mental health and substance abuse problems among employees. Such problems are a serious concern for both civilian (Danna & Griffin, 1999;Goetzel et al, 2004;Kessler et al, 1999) and military organizations (Bliese et al, 2007;Hoge et al, 2004) and can be somewhat alleviated by developing employee PsyCap.…”
Section: Mental Healthmentioning
confidence: 99%
“…To ensure that the predictor, mediator, and outcome variables were measured at three separate time points, only cases with PsyCap data measured at Time 1 (at the predeployment stage), health assessment data measured at Time 2 (immediately after deployment), and diagnosis data obtained within 120 days on return from deployment (cf. Bliese et al, 2007) were used in the current study.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…This raises the question, does this imply there has been an increase in prevalence rates of mental health difficulties within the population? Studies of US service personnel deployed to Iraq and Afghanistan have suggested a trend to increased rates of PTSD as time since deployment has increased Hoge et al, 2004;Bliese et al, 2007;Cabrera et al, 2007;Vasterling, Proctor, & Friedman, 2010). However, a different pattern has emerged in the UK.…”
Section: Differences Between Uk and Us Rates Of Mental Health Difficumentioning
confidence: 98%